Weather Information for Tribune - H. D. Bond; J. Slattery (Kansas Agricultural Experiment Station Research Reports, 2017)
In 2016, annual precipitation of 19.97 in. was recorded, which is 2.07 in. above normal. Six months had above-normal precipitation. April (5.16 in.) was the wettest month. The largest single amount of precipitation was 1.91 in. on August 7. January, the driest month, only recorded a trace of precipitation.
Keywords: weather; 2016 weather; Tribune weather